AKKELIES VAN NES, CLAUDIA YAMU - Introduction to Space Syntax in Urban Studies - Ezquerra, Isabel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Akkelies van Nes, Claudia Yamu Introduction to Space Syntax in Urban Studies Cham (Switzerland): Springer, 2021. 250 pp. Hardcover. Language: English. 51,99 € ISBN: 978-3-030-59139-7 DOI: 10.1007/978-3-030-59140-3